25 years of RIFE—a brief history and highlights. (6th December 2021) - Dewar, Alastair; Dal Molin, Franck; Clyne, Fiona; Leech, Nigel; Pemberton, Ray; Sinclair, Gillian; Toner, Mark; Wilson, Stephen; Bramley, Gillian; Thomas, Christopher; Munro, Will; Abbott, Fiona; et al.
Abstract: In 2020, the UK environmental regulators and food safety agencies, published the 25th edition of the Radioactivity in Food and the Environment (RIFE) report. This marks a quarter of a century since the landmark RIFE report was first published by the Ministry of Agriculture, Fisheries and Food in 1996, which represented the first joint monitoring and assessment report for the United Kingdom. This paper provides a summary of the RIFE report, how it has evolved and presents some case studies from over the 25 year period.